Prognostic factors after hip fracture in women with postmenopausal osteoporosis - Marcinkowska, Michalina; Horst-Sikorska, Wanda; Wawrzyniak, Anna; Dytfeld, Joanna; Hasan, Kawa Ismail; Słowiński, Krzysztof (Menopause Review/Przegląd Menopauzalny, 2012)
Background : Hip fracture is the most significant complication of osteoporosis associated with high mortality and temporary / permanent loss of physical efficiency and independence. Aim of the study : To look for factors affecting the good prognosis in patients after hip fracture. Materials and methods : The study was conducted among 120 postmenopausal women (average 76.3 years of age) surgically treated because of hip fracture. An authors’ questionnaire was given to the patients during hospitalization, one month after and 12 months after the event in order to evaluate the overall efficiency, independence and lifestyle before and after the incident. Both the time from fracture to the implementation of invasive treatment and pharmacotherapy were assessed. Results : Mortality in 12-month follow-up was 20.8%. Before the fracture, 39 women received calcium and vitamin D3, and after – 67 women. 10 women received bisphosphonates prior to the event (continued after fracture, 2 of them died), additional 5 – after the fracture. 95 women survived in the 12-month follow-up (group A), while 25 died (group B). High overall efficiency prior to the fracture was reported by 85% of group A vs. 16% of group B. Complete independence before the fracture was reported by 95% of group A versus 72% of group B. Before the injury 33% of patients in group A and 47% in group B were living alone. Patients in group A had the surgery implemented faster. Conclusions : 1. Despite surgical treatment, hip fracture still carries a high risk of death. 2. Short time of surgical intervention after hip fracture determines a good prognosis afterwards. 3. In Poland, the pharmacotherapy of overt osteoporosis is implemented far too rarely. 4. Mobility, self-dependence and living with relatives are good prognostic factors after hip fracture.